Analisis Deskriptif Perilaku Hate Speech pada Pengguna Sosial Media - Sukatin; Cindi Rahma Riadi; Fitri Wulandari; Nurul Marita; Diki Nurdwiyanto (Citra Dharma Cindekia, 2023)
A mass spread of hate speech for a specific people is a very important social issues, information technology is increasingly invading all aspects of our lives and bridging the interaction between us and society. In this globalization era, various social media platform have emerged and become a important part in our modern life. This systematic review examines a study that examined how the Internet and social media actually discourage opportunities for hate speech. A wealth of user-generated data from various social networking platforms also provides new insights for businesses and governments. The tremendous growth and convenience of the Internet, social networks, and interaction platforms offer many opportunities for building intelligent systems and communications, but by certain people or groups it is often the offensive, racist and hateful messages that make this social media spread. abused a lot.